Financing, Available Guarantees, and Earnings Quality - Azam Valizadeh Larijani (بررسی‌های حسابداری و حسابرسی)
Objective The issue of financing is a significant management topic for entities, with objectives including investment, profitability, risk reduction, and meeting the company's financial needs. Debt contracts are crucial financial resources for companies. Iranian companies typically use bank facilities or issue debt securities to outsource financing. Since financial statements are an important source of information for providers of financial resources, this research aims to examine the relationship between earnings quality and financing through bank facilities and debt securities and to compare these methods. Additionally, the research investigates the effect of the type of guarantee (bank guarantees compared to other types of guarantees) on the extent of companies' access to resources from issuing debt securities in the capital market. Methods The statistical population of this research is the companies listed on the Tehran Securities Exchange and Iran Fara Bourse from 2011 to 2022. To test the first, second, and fourth hypotheses of the research, multiple linear regression was used, and Kramer’s Z test was used to test the third hypothesis. Results The results of the research showed that there is a significant positive relationship between the earnings quality and receiving bank facilities and issuing debt securities in the capital market. As a result, by increasing the quality of accounting information and especially earnings quality, the company's access to financial resources from the providers of financial resources increases. Conclusion Therefore, company managers are advised to improve the quality of financial reporting and earnings quality to enhance their access to bank financial resources and the issuance of debt securities. Also, the results of Kramer’s Z test showed that the relationship between earnings quality and issuing debt securities is stronger than the relationship between earnings quality and receiving bank facilities. Therefore, it is recommended that the managers of companies who plan to finance through debt securities should focus on improving their financial reporting and earnings quality. This is because the Securities and Exchange Organization places considerable importance on the audited financial statements and the earnings quality at the time of granting the license to issue debt securities. In addition, the results showed that the type of guarantee (use of bank guarantees compared to other guarantees) enhances companies' access to financial resources by issuing debt securities. Therefore, it is recommended that the companies use bank guarantees when issuing debt securities if they have access to banks as guarantors, taking into account the final cost of the debt under these conditions. This is because, based on the results of this research, if bank guarantees are used, the possibility of companies accessing resources from the issuance of debt securities increases.